Prize-giving to the premium Savings Certificate holders: a Shari’ah compliance review on the Bank Simpanan Nasional (National Savings Bank) in Malaysia - Md. Sawari, Mohd. Fuad; Hassan, Razi; Abdullah, Md. Faruk (Emerald Group Publishing, 2011)
Considering the popularity of the premium savings certificate (PSC) of the National Savings Bank of Malaysia (Bank Simpanan Nasional (BSN)) the paper aims to justify the Shari’ah compliancy of this product by analyzing its underlying contracts and to propose a Shari’ah compliant savings certificate, if the current practice is invalid in the Shari’ah. Inductive methodology is first used to obtain a basic understanding of this product and the characteristics of Shari’ah approved contracts as well as the views of the jurists. Interviewing method is also used to acquire first-hand information when the inductive method is not sufficient. Afterwards, an analytical approach is adopted to justify the validity of this contract with the Shari’ah principles. Finally, an innovative methodology is used to propose a Shari’ah compliant savings certificate.The paper argues that the underlying contract used in PSC violates the conditions of wadi’ah contract, as in wadi’ah, the bank is not allowed to spend the money for investment, but in practice, BSN uses the money for investment. Therefore, the underlying contract in PSC turns into qard (loan) contract. Since the scholars unanimously declare that giving any kind of benefit like prizes to the creditor is riba, then PSC is considered as invalid according to the Shari’ah. On the other hand, although PSC might seem like gambling, it is different from gambling as the prizes given to PSC are from a third party. The paper proposes implementing mudarabah contract in PSC where the bank is allowed to invest according to its interest and the depositors share the profit and loss but the huge fluctuation of profit and loss could be shrunk by a special fund method.